The first thing that we want to do is simplify both side of this equation.
2(m-8).
The first thing we have to do, is multiple 2 by m and -8, also called distributing. So, when we do that, we get
2(m-8)=2*m + 2*-8 = 2m-16
4(m+6)
Now, we do the same thing we did for the first parenthesis, and that's multiple 4 by m and 6.
4(m+6)=4*m + 4*6 = 4m+24
Now, we need to get m by itself on one side. So, lets bring the equation from the right to the left
2m-16 = 4m + 24 (bring 4m to the other side by subtracting)
2m-16-4m = 24 (bring -16 to the right by adding)
-2m=24+16
-2m=40 (divide both sides by -2 to get your value for m)
m=40/-2 = -20
So, our answer is m = -20